Associations between serum mineral concentrations and mortality by renal function in the Ludwigshafen Risk and Cardiovascular Health Study - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Krämer, Bernhard; März, Winfried; Lorkowski, Stefan (Scientific reports, 2024)
The association of serum concentrations of minerals and phosphate with overall and cardiovascular mortality based on renal function is poorly understood. 3307 patients (average age 62.7 ± 10.6 years) in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study were grouped by estimated glomerular filtration rate (eGFR) into three categories: < 60, 60-89, and ≥ 90 mL/min per 1.73 m2, per KDIGO 2022 guidelines and were analysed using Cox regression. Low serum sodium and iron concentrations were associated with poor renal function and increased overall mortality risk, whereas higher serum zinc concentrations were associated with reduced overall and cardiovascular mortality risk. Elevated serum copper concentrations were associated with increased mortality risk across all eGFR categories. Comparing low and normal eGFR, we observed a fourfold increase in all-cause mortality risk for eGFR < 60 mL/min per 1.73 m2 and a twofold increase for eGFR 60-89 mL/min per 1.73 m2, accompanied by changes in serum mineral concentrations. The optimal range of mineral and phosphate concentrations in serum was strongly related to renal function. To reduce mortality risk, it’s important to regularly monitor serum mineral and phosphate concentrations as well as renal function, especially in cardiovascular patients with compromised renal function.